Fate of acephate and its toxic metabolite methamidophos during grape processing. (April 2018) - An, Jingjing; Gu, Xiaolin; Zhao, Xiao; Yang, Cuicui; Tabys, Dina; Xu, Yan; Liu, Ning
Abstract: This study aimed to determine the degradation of acephate and its metabolite methamidophos during different kinds of grape processing, using a simple gas-chromatographic method with a flame photometry detector. During wine processing, there was no significant effect of crushing, pressing, and clarification on the removal of acephate and methamidophos, whereas 58.9% acephate was dissipated during the fermentation step. Aging and bottling resulted in a reduction of 43.2% and 30.6% for acephate and methamidophos, respectively. The processing factors (PFs) of acephate during the wine process were <1, whereas those of methamidophos were >1. Moreover, washing with hydrogen peroxide solutions effectively reduced the levels of acephate and methamidophos present in the grape skin and pulp more than other washing solutions did (tap water, detergent solution, acetic acid solution, NaCl solution, and Na2 CO3 solution). Finally, the best removal rate of acephate residue and the minimum methamidophos level was achieved at a fermentation temperature of 22.4 °C, yeast inoculum of 8.5‰, and pH of 3.8. These results suggest that the potential metabolites of parent pesticide should be paid more attention during wine processing. Highlights: Grapes are a common fruit worldwide, consumed fresh and processed, such as wine. Acephate and methamidophos pose significant health issues to grape consumers. Hydrogen peroxide is an effective washing solution to reduce residue levels. Different wine processing steps reduce the levels of residues to varying degrees. Both the parent pesticide and its metabolite should be reduced during wine making.